Vertical motion controller design of an underwater vehicle - Ahmad Nizam, Mohd Jahari; Shahrum Shah, Abdullah; Khairul Azha, A. Aziz (2010)
This paper presents the performance of different control approaches that have been employed in controlling the vertical motion of an autonomous underwater vehicle (AUV). Different control schemes, based on conventional proportional derivative (PD) controller and an intelligent controller such as fuzzy logic (FL) controller techniques are proposed and their performance is compared. At the end of this study, the intelligent controller shows better result in term of rise time, where the conventional controller value is approximately 39.49 seconds and the intelligent controller is 35.39 seconds, respectively.